Impact of Pentecostal Churches in Social- Economic Transformation of Rural Areas in Kabale District. - Bakwengye, Deus (Kabale University, 2025)
The study research focused on the findings of the contributions of Pentecostal churches to the economic development of Uganda’s economy of Kabale district. The objectives of the study were to find out the services offered by Pentecostal churches to the economic development of Uganda’s Kabale district and to explore the challenges faced by Pentecostal churches in the transformation of rural Kabale district to find out solutions to challenges in Pentecostal churches. In chapter two, there was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on Pentecostal churches as an independent variable and the economic development of Uganda’s economy as the dependent variable. In chapter three this was where the methods of data collection were put into action. The research used both qualitative and quantitative methods of data collection and analysis. Findings of the study obtained from the field interpreting the results analyzing based on the specific objectives of the study and chapter five portrayed the summary of findings, the study concludes that the Pentecostal churches in Kabale district like to manifest themselves as advocates of social change. For bringing effective social change the first priority was to eradicate all kinds of discrimination in society, empowerment of women is the first thing to do. No doubt, the poorest women are the most disadvantaged section of society, especially because they do not have access to information and resources. So they are lagging behind in the process of development. Pentecostal churches would like to involve these women and enhance their participation in the development process and the study also recommends that Pentecostal churches work together with their government counterparts who have done tremendous work. Many churches have not only grown in size but have also developed infrastructures for research, training, and demonstration of alternative methods for increasing rural income. There were a number of successful Pentecostal churches that actively participated in the development of society by creating employment opportunities and livelihood for the poor section of the society on the Pentecostal churches and the economic development of Uganda’s economy particularly in Kabale district.